INTERPRETATION OF THE WORD KAIDAKUNNA IN Q.S. YŪSUF (12): 28 IN THE INTERPRETATION OF MARĀH LABĪD: STUDY OF MA’NA CUM MAGHZA - Sa'i, M. (Universitas Nurul Jadid, 2022)
This study reveals the meaning of the word kaidakunna in QS. Yūsuf (12): 28, and the approach used is the ma’na cum maghza theory pioneered by Sahiron Syamsuddin. This pronunciation was chosen because it has a negative connotation the meaning of deception. Several kaidun pronunciations in the Qur'an are side by side with shaitān pronunciations. Some others show the deceitful deeds of the Quraysh infidels at the beginning of Islam, and only in one place, namely in Q.S. Yūsuf (12): 28, which means deceit (seduction) of women. With the method of analysis-description-analysis as well as primary sources in the form of interpretations of the word kaidan from various commentary books and the Qur’an itself. Then secondary sources in the form of studies related to the theme of discussion, in the form of books and journals. The results of this study are, first, this verse of kaidun reveals that what is meant by deceit in the Qur’an is an act that has a hidden intention to harm other people. Second, said kaidakunna in Q.S. Yūsuf (12): 28 describes the existence of a dark side of humans (women). When covered with lust they will seduce the man they want. Third, the depth of the Qur’an through Q.S. Yūsuf (12): 28 provides advice and guidance regarding the dangers that can occur due to lust.